Denmark : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2013)
Denmark's public expenditure as a share of GDP is the highest in the OECD. The main difference between Denmark and the median OECD country is the larger amount of social protection expenditure. The public health expenditure of Denmark is the second highest in the OECD. Following years of strong public capital accumulation in facilities as well as in training, education, and research, Denmark's expenditure on public investment is now low. The composition of Denmark's expenditures is broadly in line with the high expenditure countries.